An exploratory study on space allocation of the garage as living space - Malana, Jenica Grace L.; Florendo, Raquel B. (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
ABSTRACT This exploratory study investigated the living space allotments in the garage in relation to space syntax and environmental psychology. Likewise, it determined the role of the garage as dictated by the selected middle- income households through the factors that affect their space allotment: spatial components in the house and in the living space of their garage, culture, and space perception. This study?s framework is of a multi- method research design. Fifteen (15) were handpicked to be survey respondents to access to general insights on living space allotment in the garage. Using purposive sampling, the researcher observed and documented five (5) households out of the fifteen (15) survey respondents and interviewed the primary user of the living space in each household?s garage. This research showed the possibilities of space allotment in the garage due to its open space characteristic. Different expressions of living space allotment were explored in the garage of the informant respondents: receiving area, recreational area, workspace, and niché. Though different expressions were explored, the data revealed that both the survey and informant respondents perceived the garage as mostly an entertainment/ social space followed by a space for receiving visitors and guests. The results revealed that the spatial configurations of a built environment through its architecture and spatial layout contribute to the behavioral patterns of the users of space as confirmed by space syntax. This study also raised that ventilation in the residential interior spaces of the informant respondents was a contributing factor in their living space allotment in the garage. The researcher recommends the analysis of the surrounding environment in the garage to enhance the results of the study. Additional interviews with the families of the respondents would also be an ideal action.
Thesis (B.S. Interior Design)--University of the Philippines Diliman.
Keywords: Garages -- Philippines